Probiotics and Probiotic-Derived Functional Factors—Mechanistic Insights Into Applications for Intestinal Homeostasis - Yan, Fang; Polk, D. Brent (Frontiers in Immunology, 2020)
Advances in our understanding of the contribution of the gut microbiota to human health and the correlation of dysbiosis with diseases, including chronic intestinal conditions such as inflammatory bowel disease (IBD), have driven mechanistic investigations of probiotics in intestinal homeostasis and potential clinical applications. Probiotics have been shown to promote intestinal health by maintaining and restoring epithelial function, ensuring mucosal immune homeostasis, and inhibiting pathogenic bacteria. Recent findings reveal an approach for defining previously unrecognized probiotic-derived soluble factors as potential mechanisms of probiotic action. This review focuses on the impact of probiotics and probiotic-derived functional factors, such as proteinaceous molecules, cell wall components, and probiotic metabolites, on the cellular responses and signaling pathways involved in maintaining intestinal homeostasis. Although there is limited information regarding the translation of probiotic treatment outcomes from in vitro and animal studies to clinical applications, potential approaches for increasing the clinical efficacy of probiotics for IBD, such as those based on probiotic-derived factors, are highlighted in this review. In this era of precision medicine and targeted therapies, more basic, preclinical, and clinical evidence is needed to clarify the efficacy of probiotics in maintaining intestinal health and preventing and treating disease.